Empowerment of the Tirtobakti II Farmer Group to improve production capacity of frass organic fertilizer - Winda Amilia; Andrew Setiawan Rusdianto; Miftahul Choiron (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Limited subsidized fertilizer has caused the Tirtobakti II Farmers Group to provide organic fertilizer independently. Even though the process of making organic fertilizer using fermentation is well known, the process of making organic kasgot fertilizer is the choice of KT Tirtobakti II because it is more practical and efficient. KT Tirtobakti II's kasgot production process is constrained by limited maggot production resources and limited maggot production facilities. Empowerment activities at KT Tirtobakti II aim to develop the capabilities of KT Tirtobakti II members in increasing kasgot production capacity by providing maggot feed and production facilities. Activities are carried out through a series of activities in the form of education, practice, mentoring, and evaluation. The positive impact of empowerment activities can be seen in the increasing ability of KT Tirtobakti II members to calculate the need for maggot feed ingredients according to kasgot production targets, the existence of partnership cooperation between KT Tirtobakti II and fruit and vegetable traders in traditional markets to meet maggot feed needs, and increasing production capacity by using maggot house facilities.